Interface Engineering of Fe7S8/FeS2 Heterostructure in situ Encapsulated into Nitrogen-Doped Carbon Nanotubes for High Power Sodium-Ion Batteries - Song, Penghao; Yang, Jian; Wang, Chengyin; Wang, Tianyi; Gao, Hong; Wang, Guoxiu; Li, Jiabao (Nano-Micro Letters, 2023)
Heterostructure engineering combined with carbonaceous materials shows great promise toward promoting sluggish kinetics, improving electronic conductivity, and mitigating the huge expansion of transition metal sulfide electrodes for high-performance sodium storage. Herein, the iron sulfide-based heterostructures in situ hybridized with nitrogen-doped carbon nanotubes (Fe7S8/FeS2/NCNT) have been prepared through a successive pyrolysis and sulfidation approach. The Fe7S8/FeS2/NCNT heterostructure delivered a high reversible capacity of 403.2 mAh g−1 up to 100 cycles at 1.0 A g−1 and superior rate capability (273.4 mAh g−1 at 20.0 A g−1) in ester-based electrolyte. Meanwhile, the electrodes also demonstrated long-term cycling stability (466.7 mAh g−1 after 1,000 cycles at 5.0 A g−1) and outstanding rate capability (536.5 mAh g−1 at 20.0 A g−1) in ether-based electrolyte. This outstanding performance could be mainly attributed to the fast sodium-ion diffusion kinetics, high capacitive contribution, and convenient interfacial dynamics in ether-based electrolyte. Highlights: 1 Iron sulfide-based heterostructure in situ hybridized with nitrogen-doped carbon nanotubes was prepared through a successive pyrolysis and sulfidation approach. 2 The as-prepared Fe7S8/FeS2/NCNT electrode exhibits superior sodium storage performance in both ester and ether-based electrolytes. 3 The structure advantages of the electrode contribute to high electrochemical performance in the ester-based electrolyte, while fast ionic diffusion and favorable capacitive behavior result in the robust sodium storage performance in the ether-based electrolyte.